PHYSICOCHEMICAL AND ORGANOLEPTIC QUALITY ANALYSIS OF GLUTEN-FREE WET NOODLES BASED ON SORGUM FLOUR ( SORGHUM BICOLOR L. MOENCH) - Daniel Eka Bekti Saputra; Fadjar Kurnia Hartati; Adhania Andika Prayudanti (RADJA PUBLIKA, 2026)
Dependence on wheat flour in Indonesia encourages efforts to develop local food ingredients such as sorghum which has a low glycemic index and high antioxidant content. However, the absence of gluten causes sorghum noodle dough to be less flexible and easily broken, so natural binding agents such as apple peel puree containing pectin, soluble dietary fiber, and polyphenols are needed to improve the dough structure. This study aims to analyze the physicochemical and organoleptic qualities of gluten-free wet noodles using sorghum flour as the main ingredient and the addition of apple peel puree as a source of fiber and bioactive compounds. The study used a quantitative laboratory experimental method with a Completely Randomized Design (CRD) consisting of 4 levels of sorghum flour/ S and apple peel puree/ P formulation treatments (S1P1 90:10, S2P2 80:20, S3P3 65:35, S4P4 50:50) with three replications. The parameters observed included protein content, crude fiber content, noodle flexibility, and organoleptic tests (color, aroma, taste, texture). All data were analyzed using ANOVA, if there was a significant or very significant difference, further testing was carried out. Parametric data using BNT/BNJ/Duncan depending on the KK value, while non-parametric data using Kruskal Walis test followed by effectiveness test. The results showed that the S1P1 treatment (90% sorghum flour: 10% apple peel puree) was the best treatment based on the effectiveness test with the highest yield value (NH) of 0.72. This treatment produced wet noodles with characteristics of 10.42% protein content, 1.51% crude fiber content, and tensile strength value of 0.84 N, and organoleptically preferred by panelists in the parameters of color (4.29), aroma (3.66), taste (4.49), and elasticity (4.39).